Cytotoxic Activities and Expression of Protein p53 and Bcl-2 Extract and Fraction of Inggu Leaf (Ruta angustifolia [L.] Pers) to T47D Breast Cancer Cells - Ariasti, Mia; Titik Sunarni; Wiwin Herdwiani (HM Publisher, 2024)
Inggu leaves are plants that have been traditionally used as an alternative to cancer treatment. The aim of this study was to determine the cytotoxic activity of extracts, water fraction, ethyl acetate fraction and inggu leaf n-hexane fraction (Ruta angustifolia [L.] Pers) on T47D cells and to determine the effect of protein expression of P53 and Bcl-2 genes on inggu leaf active fraction (Ruta angustifolia [L.] Pers). Extract was obtained through maceration method with ethanol 96% solvent. Ethanol extract was then fractionated with liquid-liquid partition. Cytotoxic tests were performed using T47D breast cancer cells and Vero cells with the MTT assay test method and read the absorbance on ELISA reader. To determine the effect of expression of p53 and Bcl-2, an immunocytochemistry test was carried out. The results showed that the n-hexane extract and fraction of inggu leaves had cytotoxic activity against T47D breast cancer cells with IC50 values of 54,210 and 84,118 µg/mL, while the fraction of water and ethyl acetate fractions had no cytotoxic activity with IC50 value > 100 µg / ml. Inggu leaf extract (Ruta angustifolia [L.] Pers) is able to increase the expression of p53 and inhibit the expression of Bcl-2 at concentrations of 30,19-45,54 µg/mL and n-hexane fraction can increase the expression of p53 and can inhibit the expression of Bcl-2 at concentration 49,96-75,82 µg/mL.